Tari Laku Lekuk - I Komang Aswinka Krisnanda; Anak Agung Ayu Mayun Artati; Ida Ayu Wayan Arya Satyani (Jurnal IGEL : Journal Of Dance, 2026)
Laku Lekuk is a new dance work in the form of kakebyar inspired by I Nyoman Gunarsa's painting entitled Kebyar Dancer which depicts the dynamics and beauty of Balinese dance. Based on the inspiration from this painting, the creation of this dance work aims to connect elements of fine art which include scratch painting designs with elements of traditional dance. This dance explores the relationship between body movements and strokes in Gunarsa's paintings, combining traditional and contemporary elements. The theme of this dance work is body curves, with an emphasis on body exploration as the main element with a non-dramatic presentation concept The method used in the process of creating this dance work is angripta-processan by I Kt. Suteja in his book entitled Catur Asrama; The Spiritual Climbing of Balinese People in a Dance Work. These methods include: Ngarencana, Nuasen, Makalin, Nelesin, Ngebah, Presentation (technical evaluation). The Laku Lekuk dance work involves 8 dancers and consists of three acts that reflect the interpretation of the painting and the dancer's freedom in processing body movements. This dance has 3 structures, namely round 1 (papeson), round 2 (pangawak), and round 3 (pangecet, pangipuk, pakaad). This work is accompanied by digital music or MIDI (Musical Instrument Digital Interface), with a duration of 10 minutes. This work was performed on the proscenium stage of the Natya Mandala Building, ISI Denpasar. It is hoped that this work can enrich appreciation of art, inspire the younger generation to preserve Indonesian culture, and open up space for the development of creativity in various forms of art. Keywords: Kebyar Dancer Painting, Scratches, Kakebyaran, Laku Lekuk